Fragile giants : a natural history of the Loess Hills - Mutel, Cornelia Fleischer (Bur oak original., 1989)
The Loess Hills lie in a narrow band just east of the Missouri River and define most of the western boundary of Iowa. This is the natural history of these hills of wind-deposited silt.